Kinanthropometric profile and maximum oxygen consumption in male karate athletes at different competitive levels - Almeida-Neto, P. F.; Bulhoes-Correira, A.; de Matos, D. G.; de M. Cesario, T.; das Neves, E. S.; Mousinho, G. C.; Dantas, P. M. S.; Cabral, B. G. A. T. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Kinanthropometry in karate athletes (KT) can offer advantages over maximum oxygen consumption (VO2max) during consecutive matches in competitions. Problem and Aim. To analyze the association of the kinanthropometric profile with the VO2max of KT of different competitive levels, as well as to compare the kinanthropometric profile and the performance of VO2max between athletes of different competitive levels. Methods. 36 KT adult males - 12 athletes at state level, 12 at national level (elite level) and 12 members of the control group. Their kinanthropometric profile was analyzed using anthropometry. The resting heart rate was analyzed by a oximeter. The VO2max test was performed according to the standards of Queens College Step Test. Results. National level athletes showed lower adipose tissue, superior VO2max (p <0.05) and predominant ectomorphic somatotype. The control group showed a predominance of the endomorphic somatotype. There was no relationship between the kinanthropometric profile and VO2max (p> 0.05). However, a significant effect size (ƒ²> 0.44) was reported between the kinanthropometric profile and the VO2max of KT. Conclusions. The kinanthropometric profile was not related to VO2max in KT. However, national level (elite level) KT point to a higher VO2max, less body fat tissue and greater body straightness when compared to state athletes and non-athletes.